De la dédicace au prologue du Persiles : le fin mot de Cervantès - Jean Canavaggio (E-Spania)
The two paratexts that are to be found at the beginning of the Persiles (the piece dedicated to the Count of Lemos and the reader’s prologue) offer Cervantes’ parting words. « Coloured by the consciousness of approaching death », these two outstanding pages have, during the last few years, attracted much attention and have been the object of some excellent translations. The words are examined here from the perspectives put forward for the colloquium.Dictated from his death-bed, these two texts are not simply the membra disjecta of an artist’s portrait whose truthfulness needs no verification : they are inscribed on the threshold that separates a life that comes to an end from a certain and expected death and thus disclaim Proust’s statement that held as « insincere the language of prologues and dedicatory matter ».